Prototype Desain User Interface Aplikasi My School Menggunakan Metode Lean UX - Mawar Auliya Insani; Muhamad Azrino Gustalika; Iqsyahiro Kresna (Journal of Information System Research (JOSH), 2022)
Currently, Madrasah Aliyah Negeri 2, Tangerang Regency, has problems memorizing chapter 30 as a mandatory requirement for school graduation. The system used today uses a manual and simple method by using a memorization card provided by the school. This makes students find it difficult in terms of managing the memorization track record that students take. Not only students, but teachers find it difficult because they do not have a clear track record related to memorizing juz al-Quran where the memorization card can be torn, wet and even lost. Based on these problems, technology is needed that can assist students and teachers in managing the track record of memorizing al-quran juz 30. The technology uses the Lean UX to solve problems in the User Interface My School Application Lean UX. Using the Lean UX will make it easier for the school to get faster feedback from students and develop systems that do not yet exist in the school. From the evaluation obtained, that the prototype of my school application using the lean ux method can be accepted by users because it produces a percentage of the average value of usability testing of 81% to 100%, it can be said that the category is very feasible , which is worth 82%. Then in the validity test average value is above 0.220, which means that the data is valid. Furthermore, the reliability test produces a Cronbach Alpha of 0.928, where the magnitude of the reliability factor ranges from 0 to 1, and the higher the reliability factor, the more consistent the measurement results.